New species of the Genus Mirocossus Schoorl, 1990 from Republic of Equatorial Guinea (Lepidoptera: Cossidae, Cossinae) - Yakovlev, R. V. (SHILAP Revista de lepidopterología, 2022)
The article describes Mirocossus chukovskyi Yakovlev, sp. n. (Lepidoptera, Cossidae: Cossinae), distributed in the Bioko Island (Republic of Equatorial Guinea). The article discusses the endemism in the Mount Cameroon and Bioko montane forests Ecoregion; we suggest a significant difference in the entomofauna of the insular and continental portions of the ecoregion. The article has two illustrations.